Racialized Sexual Discrimination (RSD) and Psychological Wellbeing among Young Sexual Minority Black Men (YSMBM) Who Seek Intimate Partners Online - Wade, Ryan M.; Bouris, Alida M.; Neilands, Torsten B.; Harper, Gary W. (Sexuality research & social policy, 2022)
Introduction Online dating is widespread among young adults, and particularly young sexual minority men. Racialized sexual discrimination (RSD), also known as “sexual racism,” is frequently reported to occur within these digital spaces and may negatively impact the psychological wellbeing of young sexual minority Black men (YSMBM). However, the association between RSD and psychological wellbeing is not well understood. Methods Using data (collected between July 2017–January 2018) from a cross-sectional web-survey of YSMBM ( N = 603), six multivariable regression models were estimated to examine the association between five RSD subscales and depressive symptoms and feelings of self-worth. RSD subscales were derived from the first preliminarily validated scale of sexual racism. Results Analyses revealed that White superiority ( β = .10, p < .01), same-race rejection ( β = .16, p < .001), and White physical objectification ( β = .14, p < .01) were all significantly associated with higher depressive symptoms, and White physical objectification ( β = -.11, p < .01) was significantly associated with lower feelings of self-worth. Conclusions This study is among the first to examine the relationship between multiple, distinct manifestations of RSD and depressive symptoms and self-worth using quantitative analyses and provides evidence that RSD is negatively associated with psychological wellbeing. Policy Implications Site administrators should institute robust anti-racism policies on their platforms and hold users accountable for discriminatory behavior. Activists may also consider forming coalitions and/or developing campaigns to bring about greater awareness of RSD, in an effort to influence site administrators to enact policy change.